Thromboprophylaxis in Cancer Patients - Carrier, Marc; Lee, Agnes Y. Y. (Seminars in Thrombosis and Hemostasis, 2014)
Cancer-associated thrombosis (CAT) is frequent and associated with significant morbidity and mortality among cancer patients. Hospitalized medically ill cancer patients are considered to be at high risk of CAT complications. Parenteral thromboprophylaxis with low-molecular-weight heparin is likely to reduce the risk of venous thromboembolism in this population and is recommended for the duration of the patient's hospitalization. Similarly, high-risk ambulatory cancer patients receiving chemotherapy should be made aware of their underlying risk and pharmacological thromboprophylaxis can be considered on a case-by-case basis in the absence of contraindication to anticoagulation.
Keywords: neoplasms; venous thromboembolism; venous thromboprophylaxis; heparin; low-molecular-weight heparin; bleeding